Spotlight on ORNAC Members - Switzer, Andras (Operating Room Nurses Association of Canada Journal, 2016)
Elizabeth Beck RN, CPN(C) began practicing clinical nursing in acute care settings in 1978 and began to specialize in perioperative nursing in 1997. She qualified for perioperative certification in 2008 and has performed the role of shared team leader and served as preceptor for perioperative nursing students and new staff. She also served 8 years as a Reserve Perioperative Nursing Officer (PNO) with the Canadian Forces. She is currently working as an Agency Travel Nurse as well as a casual Perioperative Nurse for Valley Regional. Her volunteer roles have included terms as the secretary and treasurer for ORNANS and her current role as the Treasurer of ORNAC (since 2014). She has 3 grown children and lives in the Annapolis Valley region of Nova Scotia with her husband.